Duvalier Regime in Haiti and Immigrant Health in the United States - Jeremy C. Green (Ubiquity Press, 2018)
Background: Haitians immigrate to the United States for many reasons, including the opportunity to escape political violence. The extant literature on Haitian immigrant health focuses on post-migration, rather than pre-migration, environments and experiences. Objective: In this study, we analyze health outcomes data from a nationally representative sample of Haitian immigrants in the United States from 1996 to 2015. We estimate age-adjusted associations between pre-migration residence in Haiti during the repressive regimes and generalized terror of Francois and Jean-Claude Duvalier, who ran Haiti from 1957 to 1986. Methods: We used ordered probit regression models to quantify age-adjusted associations between the duration of pre-migration residence in Haiti during the Duvalier regime, and the distribution of post-migration health status among Haitian immigrants in the United States. Findings: Our study sample included 2,438 males and 2,800 females ages 15 and above. The mean age of males was 43.5 (standard deviation, 15.5) and the mean age of females was 44.7 (standard deviation, 16.6). Each additional decade of pre-migration residence in Haiti during the Duvalier regime is associated with a 2.9 percentage point decrease (95% confidence interval 0.6 to 5.3) in excellent post-migration health for males, and a 2.8 percentage point decrease (95% confidence interval, 0.8 to 4.8) for females. Within the subsample of Haitian immigrants with any pre-migration residence in Haiti during the Duvalier regime, each additional decade since the regime is associated with a 3.3 percentage point increase (95% confidence interval, 1.2 to 5.5) in excellent post-migration health for males, and a 2.3 percentage point increase (95% confidence interval, 0.5 to 4.1) for females. Conclusions: Overall, we found statistically significant and negative associations between the Duvalier regime and the post-migration distribution of health status 10 to 57 years later. We found statistically significant and positive associations between the length of time since the Duvalier regime and post-migration health.